Search for invisible decays of the Higgs boson produced via vector boson fusion in proton-proton collisions at √s=13 TeV - Tumasyan, Armen; Adam, Wolfgang; Andrejkovic, Janik Walter; Borshch, Vladislav; Ivanchenko, Vladimir; Tcherniaev, Evgueni (Physical Review D)
A search for invisible decays of the Higgs boson produced via vector boson fusion (VBF) has been performed with 101 fb(-1) of proton-proton collisions delivered by the LHC at root s = 13 TeV and collected by the CMS detector in 2017 and 2018. The sensitivity to the VBF production mechanism is enhanced by constructing two analysis categories, one based on missing transverse momentum and a second based on the properties of jets. In addition to control regions with Z and W boson candidate events, a highly populated control region, based on the production of a photon in association with jets, is used to constrain the dominant irreducible background from the invisible decay of a Z boson produced in association with jets. The results of this search arc combined with all previous measurements in the VBF topology, based on data collected in 2012 (at root s = 8 TeV), 2015, and 2016, corresponding to integrated luminosities of 19.7, 2.3, and 36.3 fb(-1), respectively. The observed (expected) upper limit on the invisible branching fraction of the Higgs boson is found to be 0.18 (0.10) at the 95% confidence level, assuming the standard model production cross section. The results are also interpreted in the context of Higgs-portal models.